(untitled) (Research, Society and Development, 2021)
The application of technologies related to Industry 4.0 is already underway in countries such as the United States, Germany, China, South Korea and Japan. Given the importance of using new technologies of Industry 4.0, listed in the scientific literature, we aim to understand how international academic publications on Industry 4.0 are characterized, based on their scientific indicators. In order to meet the objective, scientific publications were extracted from the Web of Science platform and analysis techniques such as Bibliometric, Spearman Correlation and Clustering (Cluster) were used. The revelations have pointed out that the Industry 4.0 theme is recent in terms of scientific publications by the Web of Science platform. In this database, the first Management, Business and Economics academic publications took place in 2016, although from 2018 onwards, there is a significant increase of academic publications in the researched area. Empirical disclosure provided evidence that the various measurements of indicators on the Impact Factor and number of citations converge with each other. The results pointed to a gap in indicators that demonstrate academic publications with expressive citations in low-impact journals. Finally, it is pointed out that these quantitative disclosures contribute to the decision-making initial process, but with limitations, considering the importance of interpretive analysis of the scientific literature content.